THE PREREQUISITE (THE PRESUMED ELEMENT) IN THE CRIME OF TORTURING THE DEFENDANT (COMPARATIVE STUDY) - Fadel Radhi Mohammed (Scholar Express Journals, 2022)
The precondition for the crime of torture (the presumed element) is the condition that the law requires in order for the crime to take place and although it is not one of the elements of the crime, it is necessary to meet it for the commission of a crime that requires a special condition, such as the defendant being a public official or charged with a public service, and as is the case in the crime of bribery or embezzlement that requires a special element for its establishment and this precondition (supposed) must be met at the time of the perpetrator’s commencement of his constituent activity of the crime. The jurisprudence regarding it was divided into several opinions, and there were those who considered it a special condition and independent of the other elements of the crime and based this on the basis of its independence on the criminal activity of the offender because it precedes the criminal behavior that constitutes the material element, while others believe that the special elements, including the supposed element, are considered in every crime as the elements that enter into the formation of the general elements. Most crimes meet with common and general basic elements (the material element and the moral element), But this case is not the same in all of them, as there is a type of crime that is not satisfied with these two elements, but rather its legal model requires, in addition, the availability of special elements that distinguish it from other crimes, as is the case in the crime of torturing the accused to extract his confession, and these elements are represented in the characteristics of the offender and the victim and that these characteristics are related to this type of crime, whether or not, so if the offender or the victim is excluded before committing it or acquired after that, then we will be facing other crimes that have been called by other names.
Keywords: condition; presumed; torture; defendant